The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1254/jjp.41.69
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Tissue Blood Flow in Mice Loaded with SART (Repeated Cold) Stress or Restraint and Water Immersion Stress and the Effect of Administered Neurotropin

Abstract: Abstract-In order to explore the peripheral microcirculation and to obtain an outline of autonomic innervation in SARI (specific alternation of rhythm in temper ature)-stressed (repeated cold-stressed) animals, which are regarded as model animals for clinical vagotonic-type dysautonomia, peripheral tissue blood flow was determined in mice, using the hydrogen clearance method.SART-stressed mice showed a decrease in gastric blood flow, no change in hepatic blood flow and an increase in dermal blood flow. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Neurotropin has been reported to be ef fective for moderating most of the abnormal SART stress-induced symptoms (11,12,14,17,20). Similarly, the present study showed that neurotropin blocked the increased loco motor and rearing activities and defecation caused by SART stress without influencing the behavior of non-stressed rats.…”
Section: Discussionsupporting
confidence: 79%
“…Neurotropin has been reported to be ef fective for moderating most of the abnormal SART stress-induced symptoms (11,12,14,17,20). Similarly, the present study showed that neurotropin blocked the increased loco motor and rearing activities and defecation caused by SART stress without influencing the behavior of non-stressed rats.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, the microsampling system minimized catheter occlusion due to blood clots, blood loss and immobilization stress caused by manual blood sampling such as heart puncture, which led to minimal blood loss and stress when collecting multiple blood samples collection from a single animal. 28) In intravenous studies, there was no difference in the normalized AUCs and other pharmacokinetic parameters between 7.5 and 20 mg/kg, indicating that pharmacokinetics of sauchinone from 7.5 to 20 mg/kg were in the linear ranges in mice. In contrast to low doses (7.5 and 20 mg/kg), the normalized AUC was significantly greater and the CL (and CL NR ) was significantly slower, respectively, at 50 mg/kg.…”
Section: )mentioning
confidence: 88%
“…Thus, the antinociceptive effect of neurotropin was large in diseased mice compared with its effect in normal healthy mice. This fact may be related to findings that SARI-stressed animals were in the state of reduced sympathetic tone (8,11), that some of the above-described pain on which neurotropin shows analgesic effects, are thought to have some relation to the sympathetic nervous system (17)(18)(19), and that neurotropin had regulative actions on abnormal tone in autonomic nerves (20,21).…”
Section: Discussionmentioning
confidence: 99%